Fractionation of Volatile Constituents from Curcuma Rhizome by Preparative Gas Chromatography. (18th August 2011) - Yang, F. Q.; Wang, H. K.; Chen, H.; Chen, J. D.; Xia, Z. N.
Abstract : A preparative gas chromatography (pGC) method was developed for the separation of volatile components from the methanol extract of Curcuma rhizome. The compounds were separated on a stainless steel column packed with 10% OV-101 (3 m × 6 mm, i.d.), and then, the effluent was split into two gas flows. One percent of the effluent passed to the flame ionization detector (FID) for detection and the remaining 99% were directed to the fraction collector. Five volatile compounds were collected from the methanol extract of Curcuma rhizome (5 g/mL) after 83 single injections (20 uL) with the yield of 5.1–46.2 mg. Furthermore, the structures of the obtained compounds were identified as β -elemene, curzerene, curzerenone, curcumenol, and curcumenone by MS and NMR spectra, respectively.